Islamic Boarding Schools as Entrepreneurship Incubators: A Study of TMI Al- Amien Alumni Requirements - Alaillah, Fina; Hamza, Moh (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
This study aims to examine the role of Islamic boarding schools as incubators of entrepreneurship, focusing on TMI Al-Amien Prenduan Sumenep, Indonesia. It employs a qualitative case study approach to explore how entrepreneurial values are internalized and manifested among students and alumni. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model involving data condensation, display, and verification. The findings reveal that the pesantren plays a significant role in fostering entrepreneurial character through an integrated system combining value internalization, experiential learning, practical business activities, and role modeling. Entrepreneurship programs are embedded within the institutional curriculum and supported by various initiatives such as business units, skills-based activities, and mentoring. Alumni demonstrate that entrepreneurial development occurs through gradual and dynamic processes, supported by character formation, social networks, and institutional influence, while facing challenges such as limited capital and market pressures. The study concludes that pesantren function effectively as long-term entrepreneurship incubators, producing independent, adaptive, and ethically grounded entrepreneurs.